LESZEK KOCZANOWICZ, ANXIETY AND LUCIDITY: REFLECTIONS ON CULTURE IN TIMES OF UNREST - LEJZEROWICZ, MAGDA (Society Register, 2021)
In the book entitled Anxiety and Lucidity. Reflections on Culture in Times of Unrest Leszek Koczanowicz reflects upon the phenomena of fear and anxiety in essential areas of life, both for the individual as well as the community. He adopts an interdisciplinary perspective so characteristic of an insightful researcher of culture. Fear and anxiety, as he argues, are intrinsic to modernity - the inability to get rid of them is characteristic of modern man. Koczanowicz puts his thoughts on paper in a demanding fashion, which does not, however, obscure the pleasure of reading these well-written and intelligent texts. The author's knowledge is vast, which transpires in the reviewed publication.